GEOPOLITICS AND THE CONSTITUTION IN LIGHT OF THE DEMOCRATIC CONSTITUTIONAL STATE - Góes, Guilherme Sandoval (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This article is the result of research carried out in the postdoctoral stage of the Postgraduate Program in Aeronautical Sciences at the University of Aeronautics (PPGCA), whose theme was “Geopolitics, Culture and Law: Epistemological dialogues needed in times of postmodernity” Thus, it collimates to examine the scientific connections that unite geopolitics and law, disciplines that overlap in such a way that they end up guaranteeing fundamental rights for ordinary citizens, aiming to analyze the geopolitical control of law from the influence of neoliberal geopolitics on constitutionalism. of the countries of late modernity, as is the case of Brazil, thus it was possible to demonstrate the influence of real factors of world power in the legislative process of the countries of the Global South of neoliberal globalization, whose leadership is being disputed by the United States and China.